Effect of Moringa oleifera Leaf Flour Addition on Iron (Fe) and Vitamin A Levels of Crackers as a Healthy Snack - Suriyanti Suriyanti; Abd Hakim Laenggeng; Musdalifah Nurdin; Masrianih Masrianih; I Nengah Kundera; Yulia Windarsih (Biology, Medicine, & Natural Product Chemistry, 2026)
Moringa (Moringa oleifera) leaf crackers are an innovative food product that can be utilized as a nutritious snack. Moringa is widely recognized as a superfood due to its high nutritional value, including proteins, vitamins, and minerals that provide various health benefits. In the context of improving community dietary patterns, these crackers may serve as a healthier snack alternative. This study aimed to evaluate the effectiveness of Moringa oleifera leaf supplementation in increasing the iron (Fe) and vitamin A contents of crackers as a healthy snack alternative. The analyses were conducted using a spectrophotometric method with standard calibration curves to determine iron and vitamin A concentrations. The treatments consisted of different concentrations of Moringa leaf powder: 0%, 5%, 10%, and 15%. The results showed that the addition of Moringa leaf powder significantly increased the iron content, from 0.67 mg/100 g in the control treatment to 3.05 mg/100 g at the highest concentration. Vitamin A content also increased with increasing levels of Moringa leaf supplementation, although the trend was not entirely linear due to the effects of processing on compound stability. The standard calibration curves demonstrated a linear relationship between concentration and absorbance, indicating that the analytical method was valid. These findings suggest that the incorporation of Moringa oleifera leaf powder effectively enhances the nutritional quality of crackers, particularly in terms of iron and vitamin A content, making them a promising healthy snack option.